Safety of Paracetamol in Osteoarthritis: What Does the Literature Say? - Conaghan, Philip G. (Drugs Aging, 2019)
Osteoarthritis (OA) is a major cause of pain and physical disability in adults, and an increasingly common disease given its associations with aging and a growing obese/overweight population. Paracetamol is widely recommended for analgesia at an early stage in the management of OA, and, although frequently prescribed, evidence suggests the efficacy of paracetamol for OA pain is low. Furthermore, there have been recent concerns over the safety profile of paracetamol, with reports of gastrointestinal, cardiovascular, hepatic and renal adverse events. This narrative review summarizes recent literature on the benefits and harms of paracetamol for OA pain. Data on long-term paracetamol safety are derived largely from observational evidence, and are difficult to interpret given the potential biases of such data. Nonetheless, a considerable degree of toxicity is associated with paracetamol use among the general population, especially at the upper end of standard analgesic doses. Paracetamol is linked to liver function abnormalities and there is evidence for liver failure associated with non-intentional paracetamol overdose. Safety data for paracetamol use in the older population (aged >65 years) are sparse; however, there is some evidence that frail elderly people may have impaired paracetamol clearance. Given that the analgesic benefit of paracetamol in OA joint pain is uncertain and potential safety issues have been raised, more careful consideration of its use is required.